2013
DOI: 10.1155/2013/760963
|View full text |Cite
|
Sign up to set email alerts
|

JIS Definition Identified More Malaysian Adults with Metabolic Syndrome Compared to the NCEP-ATP III and IDF Criteria

Abstract: Metabolic syndrome (MetS) is a steering force for the cardiovascular diseases epidemic in Asia. This study aimed to compare the prevalence of MetS in Malaysian adults using NCEP-ATP III, IDF, and JIS definitions, identify the demographic factors associated with MetS, and determine the level of agreement between these definitions. The analytic sample consisted of 8,836 adults aged ≥30 years recruited at baseline in 2007–2011 from the Cardiovascular Risk Prevention Study (CRisPS), an ongoing, prospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 39 publications
(47 reference statements)
9
58
1
Order By: Relevance
“…Except for two studies made in India and Malaysia, the prevalence of MetS was found to be higher in both genders for IDF criteria than those for ATP III criteria in all the researches which were similar to our study (19,22). In another study conducted in Malaysia, it was reported that the prevalence of MetS was measured to be higher, as in our study and others according to the IDF definition compared to the definition of NCEP ATP III; this prevalence was also high in the analyses depending on ethnic groups (26). This condition is caused by the fact that the waist circumference, which is the central obesity criterion in IDF definition, is ≥94 cm in males and ≥80 cm in females for European region; this waist circumference varies among ethnic groups and regions and is lower for both genders compared to the NCEP ATP III definition.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Except for two studies made in India and Malaysia, the prevalence of MetS was found to be higher in both genders for IDF criteria than those for ATP III criteria in all the researches which were similar to our study (19,22). In another study conducted in Malaysia, it was reported that the prevalence of MetS was measured to be higher, as in our study and others according to the IDF definition compared to the definition of NCEP ATP III; this prevalence was also high in the analyses depending on ethnic groups (26). This condition is caused by the fact that the waist circumference, which is the central obesity criterion in IDF definition, is ≥94 cm in males and ≥80 cm in females for European region; this waist circumference varies among ethnic groups and regions and is lower for both genders compared to the NCEP ATP III definition.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, as observed in other studies, the low education level of our study group had a negative effect on the prevalence of MetS. (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 72%
“…Figure 1 shows the map of the REDISCOVER study sites. The methodology of the sampling process and recruitment has been previously described 27. The institutional ethics committee approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%
“…All interviewers and investigators were trained regarding the study procedures before conducting the study. Standardised, interviewer-based questionnaires were used to collect information regarding age, gender, ethnicity and educational attainment 27. Questions asked in the questionnaires (which were in English and Malay) included cardiovascular risk factors, past medical history, drug history, social history, physical activities and dietary history.…”
Section: Methodsmentioning
confidence: 99%
“…In countries where the federal government takes a more passive role in healthcare IT, grass roots promotion from multiple stakeholders will be necessary. In either case, providing incentives to healthcare organizations and providers will be of paramount importance in their adoption of EHR systems [6] Although Malaysia enjoys a comparatively high standard of health, [7], it is facing dilemma of chronic diseases that affect adult population [8]. However, there are only three large hospitals in Malaysiathat are capable of supporting a health information exchange (HIE) system: General Hospital, Subang Jaya Medical Centre, and Penang Adventist Hospital.…”
Section: Introductionmentioning
confidence: 99%